Application of STAD Type Cooperative Learning Models Integrated With Camtasia Studio Presentation Media on Student's Motivation and Learning Outcomes Class XI MIPA SMAN 1 Sigi Biromaru - Wagiman, Saumadin; Walanda, Daud K.; Diah, Anang Wahid M. (Universitas Tadulako, 2018)
This research aims to determine the effect of student motivation and outcomes learning through the application of cooperative learning model type of STAD combined with presentation media camtasia studio in class XI MIPA at SMAN 1 Sigi Biromaru. Subject of this research was two classes of XI MIPA1 as much 22 students as the experimental class and XI MIPA2 as much 22 students as a control class determined by Purposive Random Sampling. Data was collected use questionnaire instrument of learning motivation and learning result test. Testing data of research result using t-statistical analysis of t-test (Independent Sample t-Test) with prerequisite test that is normality test and homogeneity test. The average score of students learning motivation in the experimental class was 81 and the average score of students learning motivation in the control class was 67. The average score of students learning outcomes in the experimental class was 85 and the average score of students learning outcomes in the control class was 74. Based on the hypothesis analysis with t-test motivation of learning motivation obtained value tcount = 7.670 and it was located in the region of rejection of H0 between -2.018 and 2.018. Hypothesis analysis with t-test result statistic obtained value tcount = 8.056 and it was located in the region of rejection of H0 between -2,018 and 2.018. The result shows that there is effect of application cooperative learning model type of STAD combined with media presentation of studio camtasia toward the student motivation and outcomes learning in class XI MIPA at SMAN 1 Sigi Biromaru.